Orwell’s "Shooting an Elephant": Reflections on Imperialism and Neoimperialism - Alam, Mohammed Sarwar (IIUC Studies, 2009)
Imperialism has been the most powerful force in world history over last four or five centuries. The world has moved from the colonial to post-colonial era or neoimperialism. Throughout the period, the imperialists have changed their grounds and strategies in imperialistic rules. But the ultimate objective has remained the same- to rule and exploit the natives with their multifaceted dominance-technological, economic and military. Through dominance with these, they have been, to a great extent, successful in establishing their racial and cultural superiority. George Orwell is popularly known to be an anti-imperialist writer. This paper, I believe, will lead us to an almost different conclusion. Here, we discover the inevitable dilemma in a disguised imperialist. We discover the seeds of imperialism under the mask of anti-imperialism. In this regard, it studies his revealing short story "Shooting an Elephant". It also humbly approaches to refute Barry Hindess' arguments supporting neoimperialism. doi: 10.3329/iiucs.v3i0.2664 IIUC STUDIES Vol. - 3, December 2006 (p 5-62)